Temporal and Spatial Structure of Collective Pass-Chaining Action Performed by Japanese Top-Level Field Hockey Players - Mizawa, Takayasu; Okumura, Motoki; Kijima, Akifumi (Frontiers in Sports and Active Living, 2022)
In real hockey or soccer games, scoring opportunities usually occur quite rarely, and thus, for most of the duration of a game, the ball is drifting between the two goals. This pass-chaining situation can be regarded as the stable state of the offense–defense interaction. In the current study, temporal and spatial structure of this dynamical state was unveiled via quantification of the “defensive pressure distribution” on the pass trajectory, which was modeled as a non-linear function of the distance between the defender(s) and a given position on the pitch. Two groups, i.e., a top-level group and a less-skilled group, of Japanese collegiate hockey players were asked to play in 3-on-3 small-sided games between players of the same skill levels. When both the top-level and less-skilled players succeeded in passing the ball, there were no skill-level differences observed in the defensive pressure distribution on the pass trajectory. In these cases, the defenders put a certain level of pressure on the middle of the pass trajectory when the passer received a previously released pass, and later, when he released the ball to a teammate, the defenders approached the position at which the passer released the ball to intensively press on the passer. However, in the cases wherein they failed to thread the ball, clear differences were observed between the groups in terms of the defensive pressure distribution on the pass trajectory. In particular, for the less-skilled group, extremely intensive defensive pressure was put on the overall regions of the pass trajectory heavily concentrated on the timing at which the passer released the pass. This unique pressure distribution emerged for the less-skilled group because of their long ball-keeping duration (longer than 1 s and also longer than that for the top-level group), i.e., from the moment the passer received the ball, to the moment he released it to the next attacker. Thus, for top-level hockey players, a short time constant (less than 1 s) for the passing action will enable the passers to avoid extremely intensive defensive pressure, and enable the emergence of a dynamically stable attack–defense deadlock state through continuous chaining of the pass.